Controlled assembly and sophisticated additive manufacturing of macroscopic droplets - Yujie Yang; Huasheng Tian; Aixin Song; Lu Xu; Jingcheng Hao (Proceedings of the National Academy of Sciences, 2026)
Assembly of liquid droplets into ordered patterns and architectures has gained great interests in recent years in view of its tremendous prospects in achieving advanced biological, biochemical, and biomimetic functions. Nevertheless, current assembly techniques using lipids or colloidal particles are generally of complicated preparations, long periods, and limited droplet sizes. Here, we develop a simple and ultrafast route to assemble macroscopic water droplets into three reconfigurable structures defined as “ connection ”, “ arrest coalescence ”, and “ total coalescence ”, respectively, in dodecane using jammed nanoparticle surfactant films (termed as “POSS surfactants”) with tunable interfacial properties. Further with the POSS surfactants facilitating a sturdy and nearly instant connection between the macrodroplets, they can act as one kind of compartmentalized 3D printing inks for constructing all-liquid patterns and more integrated, sophisticated architectures capable of functioning as microreactors for transporting cargo molecules over controlled macroscale distances and dimensions. Our study can serve as a useful complement to conventional approaches that are normally used for assembling microsized droplets.